2021
DOI: 10.3390/s21082714
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Control before and after Independent Walking Onset in Children with Cerebral Palsy

Abstract: Early brain lesions which produce cerebral palsy (CP) may affect the development of walking. It is unclear whether or how neuromuscular control, as evaluated by muscle synergy analysis, differs in young children with CP compared to typically developing (TD) children with the same walking ability, before and after the onset of independent walking. Here we grouped twenty children with (high risk of) CP and twenty TD children (age 6.5–52.4 months) based on their walking ability, supported or independent walking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 56 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…To support the hypothesis, it is noteworthy to consider that different treatment approaches have shown minimal changes in synergies, even if gait pattern, movement quality and speed improved significantly after treatment ( Table 2 ). These results are coherent with the fact that CP results from a cortical and/or subcortical brain lesions in the perinatal period, causing impairments in motor controls since the very beginning ( Cappellini et al, 2016 ; Cappellini et al, 2020 ; Short et al, 2020 ; Bekius et al, 2021 ).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…To support the hypothesis, it is noteworthy to consider that different treatment approaches have shown minimal changes in synergies, even if gait pattern, movement quality and speed improved significantly after treatment ( Table 2 ). These results are coherent with the fact that CP results from a cortical and/or subcortical brain lesions in the perinatal period, causing impairments in motor controls since the very beginning ( Cappellini et al, 2016 ; Cappellini et al, 2020 ; Short et al, 2020 ; Bekius et al, 2021 ).…”
Section: Resultssupporting
confidence: 84%
“…The most affected synergies are those related to the knee-foot and the knee-hip couples, which result to be impaired in most patients ( Thelen et al, 2003 ; Czupryna and Nowotny, 2012 ). In addition, children affected by CP show a higher stride-to-stride variability, which is not observed in healthy controls ( Kim et al, 2018 ; Yu et al, 2019 ; Bekius et al, 2021 ). Bekius and others have recently summarized the evolution in the use of muscle synergies as biomarkers for evaluating locomotion in children affected by CP ( Bekius et al, 2020 ).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Comparing groups based on the VAF added by each synergy also distinguished between CON and LFH individuals, as well as HFH and LFH individuals without relying on investigator-made decisions regarding a critical threshold. A similar approach was used by Bekius et al, who found that children with cerebral palsy exhibit greater VAF in the first synergy in their more-affected side 52 . Alternatively, Ballarini et al described an algorithm for choosing the optimal NumSyn, which may also serve to decrease the impact of investigator choice on the results 53 .…”
Section: Discussionmentioning
confidence: 97%
“…Another limitation of this study is that only healthy individuals were recruited into the experiment, the obtained results cannot be extrapolated to patients with motor impaired patients directly. Because the group of disabled individuals with stroke, cerebral palsy, traumatic brain injury, and so on often display spasticity and abnormal synergy during strength training, yielding distinctly different muscle coordination patterns from that of the healthy subjects ( Kong et al, 2019 ; Bekius et al, 2021 ; Li et al, 2021 ). Therefore, in our future for subjects with specific motor impairment, the modulation of muscle synergies needs to be analyzed independently.…”
Section: Discussionmentioning
confidence: 99%